Use of calcium phosphate cement for repairing bone defects: Histomorphometric and immunohistochemical analyses - Gulinelli, Jéssica Lemos; Queiroz, Thallita Pereira; Hochuli-Vieira, Eduardo [UNESP]; Okamoto, Roberta [UNESP]; Mattos, João Marcos Borges; Calcagnotto, Thiago; Dos Santos, Pâmela Leticia (Wolters Kluwer, 2019)
This study aimed to assess the repair of surgically created bone defects filled with blood clot, autogenous bone, and calcium phosphate cement, by histomorphometric and immunohistochemical analyses. Ten adult male rabbits were used. Three bone defects were prepared with an 8-mm diameter trephine bur in the parietal region of each animal and filled with blood clot (Group BC), autogenous bone (Group AB), and calcium phosphate bone cement (Group CPC). The animals were euthanized at 40 and 90 postoperative days. The sections were subjected to histomorphometric analysis of the new bone formed inside the calvarial defects and immunohistochemical staining to determine the expression of osteocalcin (OC), osteopontin (OP), and tartrate-resistant acid phosphatase (TRAP) proteins. Histomorphometric data were analyzed statistically by analysis of variance and Tukey’s post hoc test at 5% significance level. In the results at 40 and 90 days, Group AB differed significantly from Group CPC regarding the area of newly formed bone. The immunohistochemical analysis revealed expression of OP, OC, and TRAP proteins in all groups. Group AB showed prevalence of OC and OP, and lower TRAP expression. Therefore, the calcium phosphate bone cement assessed in the present study did not accelerate the protein expression dynamics during bone healing, compared with the autogenous group.
Keywords: Autogenous bone; Bone defects; Bone substitutes; Calcium phosphate cement